Rescinding a job offer after its acceptance: The legal consequences - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia, 2017)
This article discusses the issue whether an employer is able to rescind a job offer after the same has been communicated to the employee and without suffering any legal consequences.